Comparable patient-reported outcomes in females with or without joint hypermobility after hip arthroscopy and capsular plication for femoroacetabular impingement syndrome. Issue 1 (14th March 2019) - Stone, Austin V; Mehta, Nabil; Beck, Edward C; Waterman, Brian R; Chahla, Jorge; Ukwuani, Gift; Nho, Shane J
Abstract: Hip arthroscopy is widely utilized to treat femoroacetabular impingement syndrome (FAIS). In order to evaluate the postoperative clinical and functional outcomes at 2-year follow up in patients with and without benign joint hypermobility syndrome following hip arthroscopy with capsular plication for FAIS, consecutive female patients with generalized ligamentous laxity undergoing primary hip arthroscopy with complete T-capsulotomy closure via plication for FAIS were prospectively identified. Patients were matched in a 4:1 ratio based on Beighton-Horan joint mobility index (BHJMI) then classified into no generalized joint laxity (NGJL, Score<4) or generalized joint laxity cohort (GJL, Score=4). Patient and surgical-related factors were analyzed using univariate and paired analysis with statistical significance set at a = 0.05. A total of 125 female patients were included in the study: 25 generalized joint laxity (GJL) patients and 100 matched to age, sex and BMI (NGJL cohort). The results demonstrated that there were no significant differences between demographics, preoperative range of motion, or radiographic analysis on univariate analysis. There was no statistical difference in postoperative range of motion between groups, though both groups demonstrated significant increases in postoperative flexion and postoperative internal rotation following hip arthroscopy. Paired analysis demonstrated no significant difference in HOS-SS, HOS-ADL, mHHS or VAS-pain, while GJL patients reported significantly greater patient satisfaction score at 2-years follow-up (p=0.007). In summary, hip arthroscopy with capsular plication is a highly effective treatment for FAIS in patients with and without generalized joint laxity. In our analysis, patients with and without generalized joint laxity demonstrated statistically similar and significant improvement in outcomes.